Mutations in degP and spoT Genes Mediate Response to Fermentation Stress in Thermally Adapted Strains of Acetic Acid Bacterium Komagataeibacter medellinensis NBRC 3288 - Kataoka, Naoya; Matsutani, Minenosuke; Matsumoto, Nami; Oda, Misuzu; Mizumachi, Yuki; Ito, Kohei; Tanaka, Shuhei; Kanesaki, Yu; Yakushi, Toshiharu; Matsushita, Kazunobu (Frontiers in Microbiology, 2022)
An acetic acid bacterium, Komagataeibacter medellinensis NBRC 3288, was adapted to higher growth temperatures through an experimental evolution approach in acetic acid fermentation conditions, in which the cells grow under high concentrations of ethanol and acetic acid. The thermally adapted strains were shown to exhibit significantly increased growth and fermentation ability, compared to the wild strain, at higher temperatures. Although the wild cells were largely elongated and exhibited a rough cell surface, the adapted strains repressed the elongation and exhibited a smaller cell size and smoother cell surface than the wild strain. Among the adapted strains, the ITO-1 strain isolated during the initial rounds of adaptation was shown to have three indel mutations in the genes gyrB, degP, and spoT. Among these, two dispensable genes, degP and spoT, were further examined in this study. Rough cell surface morphology related to degP mutation suggested that membrane vesicle-like structures were increased on the cell surface of the wild-type strain but repressed in the ITO-1 strain under high-temperature acetic acid fermentation conditions. The degP strain could not grow at higher temperatures and accumulated a large amount of membrane vesicles in the culture supernatant when grown even at 30 °C, suggesting that the degP mutation is involved in cell surface stability. As the spoT gene of ITO-1 lost a 3’-end of 424 bp, which includes one (Act-4) of the possible two regulatory domains (TGS and Act-4), two spoT mutant strains were created: one (TGSAct) with a drug cassette in between the 5’-half catalytic domain and 3’-half regulatory domains of the gene, and the other (Act-4) in between TGS and Act-4 domains of the regulatory domain. These spoT mutants exhibited different growth responses; TGSAct grew better in both the fermentation and non-fermentation conditions, whereas Act-4 did only under fermentation conditions such as ITO-1 at higher temperatures. We suggest that cell elongation and/or cell size are largely related to these spoT mutations, which may be involved in fermentation stress and thermotolerance.